2020
DOI: 10.1177/0141076820962068
|View full text |Cite
|
Sign up to set email alerts
|

Anger and confrontation during the COVID-19 pandemic: a national cross-sectional survey in the UK

Abstract: Objectives To investigate factors associated with anger or confronting others due to COVID-19. Design Online cross-sectional survey. Setting Data were collected between 17 and 20 July 2020. Participants A total of 2237 participants living in the UK aged 16–75 years. Main outcome measures Reporting having had arguments, felt angry or fallen out with others because of COVID-19. Reporting having confronted or reported someone to the authorities, or that you had been confronted or reported to the authorities, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 26 publications
(38 reference statements)
4
56
0
Order By: Relevance
“…The literature supports the experiences reported. Stokes et al 9 reported 36 % of patients experienced myalgia, 43.4% experienced headache, and 10 percent reported a loss of taste and smell. Other studies reported a greater incidence of changes in taste and smell.…”
Section: Discussionmentioning
confidence: 98%
“…The literature supports the experiences reported. Stokes et al 9 reported 36 % of patients experienced myalgia, 43.4% experienced headache, and 10 percent reported a loss of taste and smell. Other studies reported a greater incidence of changes in taste and smell.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies on anger during the COVID‐19 outbreak were found in a review of the literature. In a study conducted by Smith, Duffy, et al ( 2020 ) 56% of participants reported arguing with others and feeling angry or struggling with others as a result of COVID‐19. Today, with the outbreak of COVID‐19, which can cause problems such as anxiety and anger in the community and have an impact on people's mental health, mental health care has been recommended, and mental health problems should be treated if necessary (Landi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, despite in many cases being necessary, several public health responses to the pandemic were still severe disruptions to individuals' economic, social, and personal lives. As a result, multiple stakeholders held conflicting incentives and ideas about the high-stakes issue of the best course of action, which frequently led to angry confrontations between values and politicization (Gadarian et al, 2021;Pew, 2021;Smith et al, 2021;Trevors & Duffy, 2020). Taken together, the infodemic and the strong emotional reactions it elicited presented a historic challenge to public health communication, which provided space for misconceptions to proliferate 1 and necessitated new approaches to public education (Han et al, 2020;Li et al, 2020).…”
Section: Infodemic Contextmentioning
confidence: 99%